2022
DOI: 10.1128/spectrum.01734-22
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Peptidoglycan Carboxypeptidase DacA on Intrinsic β-Lactam and Vancomycin Resistance

Abstract: Bacterial PG hydrolases play important roles in various aspects of bacterial physiology, including cytokinesis, PG synthesis, quality control of PG, PG recycling, and stress adaptation. Of all the PG hydrolases, the role of PG carboxypeptidases is poorly understood, especially regarding their impacts on antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…The role of the C-terminal membrane-anchoring domain of DacA was also analyzed. A previous report showed that PG carboxypeptidase activity of DacA(ΔC) was significantly higher than that of WT DacA (Park et al , 2022). DacA(ΔC) did not complement the alkaline and salt sensitivities of the dacA mutant or morphological defects in LB medium (Figure 3).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…The role of the C-terminal membrane-anchoring domain of DacA was also analyzed. A previous report showed that PG carboxypeptidase activity of DacA(ΔC) was significantly higher than that of WT DacA (Park et al , 2022). DacA(ΔC) did not complement the alkaline and salt sensitivities of the dacA mutant or morphological defects in LB medium (Figure 3).…”
Section: Resultsmentioning
confidence: 83%
“…In a previous study, we demonstrated that DacA directly interacts with PBPs in a C-terminal domain-dependent manner (Park et al ., 2022). To determine whether these interactions are also detected between DacC and PBPs, we performed pull-down experiments using DacC-Flag and DacC(ΔC)-Flag strains expressing His-tagged or non-tagged PBPs.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations